Strategic Financial Management in Entrepreneurial Ventures: A Comprehensive Qualitative Review of Financial Practices and Their Impact on Startup Growth and Stability - Ma'ruf Idris, M. (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study investigates the impact of strategic financial management practices on the growth and stability of entrepreneurial ventures, with a particular focus on startups. Employing a qualitative research methodology, this analysis synthesizes insights from a comprehensive review of existing literature alongside case studies to elucidate the effective financial management strategies that startups can leverage to navigate their unique market challenges. The research method involves detailed interviews with financial managers and startup founders, along with an analysis of financial documents and performance metrics across diverse industry sectors. The findings reveal that effective capital structuring, innovative funding mechanisms such as crowdfunding, adept cash flow management, and precise financial forecasting are pivotal to startup stability and growth. Capital structuring that balances debt and equity optimally reduces financial risk and enhances attractiveness to investors. Crowdfunding not only garners capital but also facilitates market validation and community engagement, contributing to both financial and operational stability. Effective cash flow management emerges as a critical determinant of liquidity and operational continuity, while advanced financial forecasting supports strategic adaptability in the volatile startup environment. Overall, the study confirms that strategic financial management tailored to the nuanced needs of startups significantly contributes to their sustainability and growth. These findings provide both theoretical expansions on traditional financial management theories and practical insights for startup management and policy-making.